Influence of Celebrity Endorsement on Consumers’ Buying Behavior of Fast Moving Consumer Goods in Kathmandu - Pokharel, Aradhana; Pradhan, Binit (Journal of Business and Social Sciences Research, 2018)
This paper explores the influence of celebrity endorsement on consumers’ buying behavior of Fast Moving Consumer Goods (FMCG). It aims to analyze the influence of celebrities’ attributes (attractiveness, expertise, trustworthiness, popularity) on the buying behavior of people living in Kathmandu valley. The entire information are collected using structured questionnaire from one hundred and fifty respondents in Kathmandu valley. The results of descriptive analysis reveal that celebrity endorsement does have positive impact on buying behavior of majority of people. It has also been identified from the study that respondents ranked brand as the most dominant factor influencing their buying behavior whereas they ranked celebrity endorsement as forth priority. The result of inferential analysis reveals that significant relationship exists between celebrities’ attributes and purchase intension of FMCG. Since Nepali FMCG companies are in dire need of good promotional strategy, this study provides useful insight to FMCG companies and marketers in Nepal. Journal of Business and Social Sciences Research, Vol. 2, No. 1 & 2, pp. 1-14